Idiopathic hypoparathyroidism: A case study - Ahmed, Yousif B. (Zanco Journal of Medical Sciences (ZJMS), 2014)
Background and objective: Hypoparathyroidism is an uncommon endocrine-deficiency disease characterized by low serum calcium levels, elevated serum phosphorus levels, and absent or inappropriately low levels of parathyroid hormone in the circulation. It is characterized by carpal and pedal muscle spasms, positive Chvostek's and Trousseau's signs. Diagnosis is done by typical clinical and laboratory findings. Current treatment options include oral calcium, vitamin D, and thiazide diuretics. We present a 21 years old girl exhibiting characteristic features of idiopathic hypoparathyroidism presented with nonunion fracture of right ulner bone.